Government Policies in Resolving Conflicts between Traditional Markets and Online Markets from A Maqashid Sharia Perspective - Hisyam Ramadhan; Syaifuddin Zuhdi (Universitas Muhammadiyah Surakarta, 2025)
In social psychology, there are various ways for people to lead fulfilling lives. There are those who use peaceful paths such as dividing groups, but there are also those who use violent paths such as invading a territory. There are several reasons why traditional educators hesitate to recommend Tiktok Shop to the government. One reason is that people are more comfortable making purchases online. Events that occur in traditional markets and those that occur online can be likened to Islamic sayings based on the Qur'an, Hadith, Ijma, and Qiyash. Descriptive and normative analysis methods will provide clear and concise results as well as examples or actions that can be a springboard for further research. Trade in goods was developed between 1457 and 1540 B.C.. According to article 1457 B.W. According to Syatibi, one way to understand and comprehend maqashid al-syariah is to analyze the lafaz of commands and prohibitions (al-awamir wa an-nawahi) contained in the law. This is because the purpose of prohibitions and orders is to promote health and prevent damage. One of the things that often happens in human life is dispute. Disputes are also a little point of view on problems that arise and cause disruption of living standards because humans are social creatures. The presence of unreliable payment systems in online markets, also known as online marketplaces, causes online shop users who connect with each other through these marketplaces to feel less connected to each other than in traditional markets. Social discord indicates that they experienced social discord and eventually led to the conflict. Their economic weakness is that their sales have decreased since the establishment of online stores in Indonesia. The downside of their technology is that people in traditional markets are not ready to learn and keep up with the rapid advancement of modern technology. Islam teaches us that all truth is in the hands of Allah, and the righteous will always be able to overcome evil. A lack of sense of responsibility makes people feel uncomfortable, especially caretakers of public facilities. There are so many laws that talk about this, mostly about consumer privacy rights when making a purchase or sale.